Urgensi Stabilitas Politik Hukum Dalam Pembentukan Tujuan Negara - Glica Aini Suniaprily, Firstnandiar; Nurwanti, Yulian Dwi; Nugraha, Adhy (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
The definition of legal politics continues to develop with various formulations by several legal experts who have been observing the development of the discipline. There are several legal experts who give their views on the definition of legal politics including: Teuku Muhammad Radhie, conceptualizes legal politics as a statement by the state ruler about the law that applies to the territory of a country and about the direction in which state policy is to be developed. This normative-empirical research method is about the implementation of normative legal provisions (Law) in action on every specific legal event that occurs in a society. In this research there are three categories, namely: Non Juridical Case Study (legal case study approach without conflict so that there is no intervention with the court), Juridical Case Study (legal case study approach due to conflict so that it will involve intervention with the court providing a settlement decision [jurisprudence]), and Live Case Study (approach to a legal event whose process is still ongoing or has not ended). The role of legal politics in the development of national law in Indonesia cannot be separated from the historical context. As is known, after Indonesia's independence until after the reformation, the Indonesian people have tried to improve the national legal system in accordance with the current development of the Indonesian state. Throughout the history of Indonesia, there have been alternating political changes based on periods of political systems between democratic and authoritarian politics. In line with these political changes, the character of legal products has also changed. The occurrence of these changes is because the law is a political product, so the character of legal products changes when the politics that gave birth to it changes. To get the maximum legal objectives according to Satjipto Rahardjo, it is built with the term Progressive Law, which is dependent on human ability to reason and understand and human conscience to make legal interpretations that prioritize the moral value of justice in society. Various political experts define legal politics based on the meaning of the meaning of the law itself, including Padmo Wahjono who defines legal politics as a policy in state administration regarding what is used as a criterion in punishing a policy such as determining the direction, form, and content of a law.